(3TQM GdYVOjI fXe GdBOGHs - (3GdMjOQj GdUahj GdMSjf BHGOj, aUjM GdOjf, aUjM, EHQGgje Hf UHZI Gddg Hf CSYO, J (B1299 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO def dG jYGQV Mceg CMlO gPg JMbjbGJ TQjaI hJObjbGJ dWjaI YdbJgG Ydi fXe GdMfajI aj GdBOGH dHYV Phj GdCdHGH Mjf JQGce Gdgehe hUO GdCgd Yfj hGdCUMGH CJhSd HgG dQaY gej hcTa Zej s
(3BNQgG (B:s
(3hbGd GdTgQSJGfj aj fgGjI GdEbOGe Cf GdcdGe GdfaSj gh CeQ bGFe HPGJg JYGdi TGed ddaX hGdeYfi LejYG ZjQ eQJH GdCLRGA cGdbGFe HfaS GdMGaX hGdJQJjH EfeG gh aj GdJdaX hbO Je GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/44s
(3gOjI GdYGQajf (B1/23s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs